Lakefront : public trust and private rights in Chicago - Kearney, Joseph D.; Merrill, Thomas W. (Cornell University Press, 2021)
"A history of how Chicago's lakefront, with its parkland and Lake Shore Drive, has come to be. Beginning with the mid-nineteenth century, this book considers both local and broader social, economic, and legal forces, with particular emphasis on the conflict between public and private rights"-- Provided by publisher
Keywords: Lakeshore development -- Illinois -- Chicago -- History.; Lakeshore development -- Social aspects -- Illinois -- Chicago.; Lakeshore development -- Economic aspects -- Illinois -- Chicago.; Lakeshore development -- Law and legislation -- Illinois -- Chicago.; Rives -- Aménagement -- Illinois -- Chicago -- Histoire.; Rives -- Aménagement -- Aspect social -- Illinois -- Chicago.; Rives -- Aménagement -- Aspect économique -- Illinois -- Chicago.; ARCHITECTURE -- Urban & Land Use Planning.; Lakeshore development; Lakeshore development -- Law and legislation; Illinois -- Chicago; Chicago lakefront, History of Lake Shore Drive, Chicago's Lake Michigan shoreline, Montgomery Ward, Streeter/Streeterville, Grant Park.; History